CORRELATION OF SERUM FERRITIN, HEMOGLOBIN, AND PLATELET LEVELS IN PREGNANT WOMEN WITH GESTATIONAL DIABETES - Nasir, Sallama Kamel; Mahmood, Sara Shakir; Ali, Rezan Abdulrahman (Journal of Sulaimani Medical College, 2022)
Background Gestational diabetes mellitus (GDM) affects approximately 7% of all pregnancies. Pregnancy which is regarded as a pro-inflammatory state “mostly because of the mitochondria-rich placenta,” is a condition that favors oxidative stress. A transitional metal, particularly iron, abundant in the placenta, is significant in producing free radicals. Various studies indicate that free radicals play a remarkable role in GDM. Iron storage and status in the body can be reliably assessed by serum ferritin as the standard measurement. Objectives The present study aimed to measure the serum ferritin level, hemoglobin, and platelet count in women with GDM and compare it with those of women experiencing a normal pregnancy. Patients and Methods This case-control study was conducted in Sulaimani Maternity Teaching Hospital in Sulaimani city, Iraq. Over 18 months, they were starting from Jan 1, 2020, till Jun 30, 2021. The study sample consisted of 160 pregnant women in the third trimester of their pregnancy. The participating women were divided into a study group and a control group. The study group consisted of 80 pregnant women with GDM, which OGTT detected from 24 to 28 weeks of their pregnancy. The control group consisted of 80 pregnant women who had a normal and healthy pregnancy, did not have GDM, and were in their third trimester. For both groups, mean platelet volume, platelet count, hemoglobin level, and serum ferritin level were measured, and the two groups were compared in terms of these variables. Results Compared to the control group, the group with GDM had a significantly higher level of mean serum ferritin (29.04±16.09 ng/ml versus 37.97±29.42 ng/ml) (P=0.02). However, the study and control groups were not statistically different regarding their mean hemoglobin levels (12.26±0.63g/dl versus 12.14±0.60g/dl) (P-value=0.19). In addition, the study group had a significantly higher mean platelet count than the control group (246.71x 103/µl±54.02 versus 203.52 x103/µl±54.1) (P<0.001). However, no significant difference was seen between the study group and the control group regarding their mean platelet volume (MPV) (9.50±1.25 1015/L versus 9.35±0.95 1015/L) (P=0.41). Conclusion Compared with women with normal pregnancy, GDM women have higher serum ferritin levels and platelet count; therefore, serum ferritin can be regarded as a marker for GDM pathogenesis. However, it is recommended that serum ferritin levels should be measured in early pregnancy to evaluate the risk of GDM development in those with high serum ferritin levels.
Keywords: Gestational diabetes; serum ferritin; hemoglobin; platelet count